Women Language Found in Falling Inn Love Movie - Prizelia , Devya Ayu; Putri, I Gusti Ayu Vina Widiadnya; Putra, I Gusti Bagus Wahyu Nugraha (Institut Pariwisata dan Bisnis Internasional, 2023)
This study discusses about women’s language features that occur in the utterance of the main character from the Falling Inn Love movie. The aim of this study was to analyze women’s language features and the function of each feature that are used by the main character or Gabriela through the utterance by applying the main theory by Lakoff (1975) and Pearson (1985). In conducting the data, this study was using the descriptive qualitative method to organize the description of the data result. In presenting the data this study was using formal and informal methods. It was found nine out of ten features were used by the main character. The most feature that occurs in the main character utterance was lexical hedges or filler (25%) while the least feature that occurs in the dialogue was emphatic stress and hypercorrect grammar (2, 50%). Almost all the features by Lakoff (1975) are found in this movie except precise colour terms.